The effect of the mold cavity feeding mode on the structure and crystallinity of HD-PE - Bociąga, E. (Polimery, 2022)
Injection molding of large and complex-shaped parts involving the multipoint cavity feeding mode, gives rise to the formation of weld lines which degrade the mechanical properties of the product and the quality of its surface. The structure (as established by scanning microscopy) and the degree of crystallinity (Sk, as determined by DSC) examined along the axis of injection molded parts, were studied in Dow Chemicals type 10262A HDPE, in relation to single- (I) or double-gated (II) cavity feeding mode. With cavity II, the weld line area disclosed a heterogeneous structure (Fig. 3). With cavity I, the degree of crystallinity rose as the distance from the gate was prolonged (Fig. 4a); with cavity II, the degree of crystallinity was lower in the areas close to the gate and in the middle of the sample where weld lines were created (Fig. 4b). Mold cavity design should take care to predict weld line areas, because suppressed crystallinity is known to result in deteriorated mechanical properties.